Interaction of light with hematite hierarchical structures: Experiments and simulations. (March 2017) - Distaso, Monica; Zhuromskyy, Oleksander; Seemann, Benjamin; Pflug, Lukas; Mačković, Mirza; Encina, Ezequiel; Taylor, Robin Klupp; Müller, Rolf; Leugering, Günter; Spiecker, Erdmann; Peschel, Ulf; Peukert, Wolfgang
Abstract: Mesocrystalline particles have been recognized as a class of multifunctional materials with potential applications in different fields. However, the internal organization of nanocomposite mesocrystals and its influence on the final properties have not yet been investigated. In this paper, a novel strategy based on electrodynamic simulations is developed to shed light on how the internal structure of mesocrystals influences their optical properties. In a first instance, a unified design protocol is reported for the fabrication of hematite/PVP particles with different morphologies such as pseudo-cubes, rods-like and apple-like structures and controlled particle size distributions. The optical properties of hematite/PVP mesocrystals are effectively simulated by taking their aggregate and nanocomposite structure into consideration. The superposition T-Matrix approach accounts for the aggregate nature of mesocrystalline particles and validate the effective medium approximation used in the framework of the Mie theory and electromagnetic simulation such as Finite Element Method. The approach described in our paper provides the framework to understand and predict the optical properties of mesocrystals and more general, of hierarchical nanostructured particles. Highlights: A strategy for rigorous shape and size control of hematite mesocrystals is shown. Electrodynamic simulations are used to model their extinction properties. An excellent agreement with experimental spectra sheds light on their internal structure. The method allows predicting the extinction properties of hematite mesocrystals.